An Analysis of the Economic Solutions as in the Kutadanta Sutta: A Case Study of Chim Shop Chai Project - et. al., Phrapalad Somchai Damnoen, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This Article aimed to analyze the economic solutions of the Chim Shop Chai Project in accordance with the Kutadanta Sutta’s principles. This is a qualitative as documentary research. It has been conducted through Thai Tipitaka scriptures, books, documents, academic papers, and various researchers. The findings showed that 1) Solving the economic problems based on the Kutadanta Sutta principles was to solve macroeconomic problems. The way to do this was to provide funding to 3 groups of people who are diligent in their careers, namely farmers, merchants, and government officers. 2) The Chim Shop Chai Project aimed to stimulate the economy through domestic tourism promotion. 3) the economic solution analysis of the Chim Shop Chai Project in accordance with the Kutadanta Sutta’s principles showed that the Chim Shop Chai Project has the same principles as the Kutadanta Sutta in 2 cases: (a) The government wanted to alleviate economic trouble for their people by giving money to the people. (b) The government wants economic circulation according to the principles of macroeconomics resulting in increased purchasing power in the country. For the differences, It is found that the government did not select participants in to the program according to the occupational groups but allowing all professions to participate in the program freely. Not only participants who are low income, but the high-income people can also join. The government therefore does not promote production factors for farmers in any way. When this happens, it is still not to encourage those who are diligent in their careers as exemplified in. Only merchants who are registered for this project will benefit directly from this project.